Academic Leadership for Teaching and Research Development in Higher Education: A Bahraini Case Study - AL-Qallaf, Amal Jasim (2016)
The Arabian Gulf countries have witnessed a significant growth and development in higher education provisions and demands since the end of 1980s. The main purpose of this study is to gain a better understanding of the experiences and roles of academic leadership administrators in higher education in the Kingdom of Bahrain while enhancing teaching and research quality, and investigating the current quality management model used for effective leadership, and what style of leadership best handles the challenges of cultural diversity within Bahraini higher educational organizations especially in their early stages of development in order to reach world standards development. A composite theoretical framework was designed using Bolden, Petrov, and Gosling (2008) academic leadership model, Trompenaars and Hampden-Turner’s (1998) and Branine’s (2011) models of cross-cultural management, Schein’s (2004) model of organizational culture and leadership, Schultz’s (1995) model of organizational culture and Shils’s (2008) academic ethos for teaching and research. The methodology used in this study is a predominantly qualitative and interpretive case study, using mixed methods which included the following: International, regional, national, and organizational document analysis; interviews with Deans, Chairs, and Quality Assurance Authority representatives; a faculty survey; and alumni focus groups. There are two main types of results. The first is empirical, finding that there is a rich potential for research in Bahrain but funding, heavy workloads and more advanced training are the main obstacles, whereas for teaching the strength is in the academics’ quality of teaching but workload is the single most important problem, and for leadership the strength is in the quality of expertise but are constrained by lack of autonomy. The second main result of the study is the development of a more comprehensive, regionally appropriate, and multi-dimensional model for university development that includes: academic leadership and organizational dimensions, the academic ethos elements; the multicultural interactions dimension; the dynamic system Interaction; the integrated model, and the temporal domains/changes and developmental. This model aims to contribute to the development of an academic system that best suits higher education institutions in the Kingdom of Bahrain.